Molecular Cloning and Functional Characterization of the Dehydrin (IpDHN) Gene From Ipomoea pes-caprae - Zhang, Hui; Zheng, Jiexuan; Su, Huaxiang; Xia, Kuaifei; Jian, Shuguang; Zhang, Mei (Frontiers in Plant Science, 2018)
Dehydrin (DHN) genes can be rapidly induced to offset water deficit stresses in plants. Here, we reported on a dehydrin gene (IpDHN) related to salt tolerance isolated from Ipomoea pes-caprae L. (Convolvulaceae). The IpDHN protein shares a high amino acid sequence similarity with Arabidopsis dehydrin ERD14 (At1g76180). IpDHN was shown to have a cytoplasmic localization pattern. Quantitative RT-PCR analyses showed that IpDHN was constitutively expressed in different organs of I. pes-caprae plants, and its expression level increased after salt, osmotic stress, oxidative stress, cold stress and ABA treatments. Analysis of the 974-bp promoter of IpDHN identified distinct cis-acting regulatory elements, including an MYB binding site (MBS), ABRE (ABA responding)-elements, Skn-1 motif, and TC-rich repeats. The induced expression of IpDHN in Escherichia coli indicated that IpDHN might be involved in salt, drought, osmotic, and oxidative stresses. We also generated transgenic Arabidopsis lines that over-expressed IpDHN, and we carried out salt and drought stress assays. The transgenic Arabidopsis plants showed a significant increase in tolerance to salt/drought stresses and less accumulation of hydrogen peroxide (H2O2) and the superoxide radical (O2−), accompanied by increasing activity of the antioxidant enzyme system in vivo. Under osmotic stresses, the overexpression of IpDHN in Arabidopsis can elevate the expression of ROS-related and stress-responsive genes and can improve the ROS-scavenging ability. Our results indicated that IpDHN is involved in cellular responses to salt and drought through a series of pleiotropic effects that are likely involved in ROS scavenging and therefore influence the physiological processes of microorganisms and plants exposed to many abiotic stresses.